Analisis dan Usulan Perbaikan Dengan Metode 5S Pada Departemen Fabrikasi PT SPPA - Satria Hadi Wibowo; Abdul Alimul Karim; Sigit Rahmat Rizalmi (Fakultas Rekayasa dan Teknologi Industri, 2024)
PT SPPA is a company that deals with the repair of mining components or heavy equipment. The company serves repairs and inspections of various types of machines, such as generators, welding machines, compressors, water pumps, and tractors. The fabrication department needs improvement in terms of structuring the work environment, especially in the toolkit area. The fabrication department is a part of the company which in carrying out its duties includes fabrication works such as material surface smoothing, component welding, the process of unification between parts in an item. In the area where the toolkit is located, it can be seen that the area is not well-organized, such as a hose that is not properly coiled, equipment collected on a large scale, and also there are still some unused items that give the impression of filling the space area of the toolkit. Therefore, a proposal for improvement is made using the 5S method, namely Seiri, Seiton, Seiso, Seiketsu, Shitsuke or can be interpreted as Concise, Neat, Clean, Treat, Diligent. This method can be used to produce a higher quality work area related to these five aspects, so as to reduce or eliminate the time to look for equipment in it. Then, suggestions for improvements through 3D designs are also generated based on previous evaluations regarding the similarity of item functions.